2018
DOI: 10.1155/2018/8134918
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Yinchenhao Decoction on Cholesterol Gallstone in Mice Fed a Lithogenic Diet by Regulating LXR, CYP7A1, CYP7B1, and HMGCR Pathways

Abstract: The study attempted to elucidate whether lipid genes are closely associated with lipid metabolic abnormalities during the lithogenic time and how Yinchenhao Decoction (YCHD) works on the transcriptions of lipid genes against cholesterol gallstone model. C57BL/6J mice fed on lithogenic diet (LD) were used for model establishment and randomized into 5 groups. All groups received LD for different weeks with isometrically intragastric administration of YCHD or NS. Biochemical tests were measured and liver tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Yinchenhao decoction [142], and ellagic acid [143]. These agents may be worth testing for their effectiveness in reducing early inflammatory responses in NAFLD.…”
Section: Targeting Mitochondrial Cholesterol Metabolites For Nash Int...mentioning
confidence: 99%
“…Yinchenhao decoction [142], and ellagic acid [143]. These agents may be worth testing for their effectiveness in reducing early inflammatory responses in NAFLD.…”
Section: Targeting Mitochondrial Cholesterol Metabolites For Nash Int...mentioning
confidence: 99%
“…YCHD has been found to have a significant impact on various indicators, including sodium taurocholate cotransporting polypeptide, multidrug resistance protein 1, bile salt export pump, organic cation transporter 1, and organic anion transporter 1A2, leading to their increase. Furthermore, YCHD can regulate the main metabolic pathway of phase II, which inhibits the increase of naphthalene isothiocyanate content[ 98 ].…”
Section: The Treatment Of Oj: Medication and Surgerymentioning
confidence: 99%
“…Liver X receptor α (LXRα), an oxysterol-binding transcription factor, which regulate the transcription level of CYP7A1 . CYP7A1 was downregulated with lithogenic time progressed, while CYP7A1 mRNA was increased 3-fold under the treatment of Yinchenhao Decoction, and revealed that CYP7A1 mRNA may be efficient targets of Yinchenhao Decoction, which may be a preventive medicine against cholesterol gallstone formation (Meng et al 2018). CYP7A1 mediate the transformation of cholesterol into bile acids in vitro.…”
mentioning
confidence: 96%